Cytokine modulation in pelvic organ prolapse and urinary incontinence: from molecular insights to therapeutic targets - Yongxiu Chen; Amin Ullah; Weifang Chen; Jianyan Xuan; Xiaowen Huang; Shiqi Liang; Bairong Shen; Tingfeng Wu (BMC, 2024)
Abstract Pelvic organ prolapse (POP) and urinary incontinence (UI) are common disorders that significantly impact women's quality of life. Studies have demonstrated that cytokines, including pro- and anti-inflammatory immune mediators, play a role in illness genesis and progression. Research on the inflammatory milieu of the pelvic floor has shown that POP patients have increased inflammation in vaginal tissues. This evidence revealed that significant changes in the inflammatory milieu of the pelvic floor are an aspect of the pathogenesis of POP. POP patients exhibit increased levels of inflammatory cytokines (IL-1, TNF, IFN, and others) in the front vaginal wall, which may alter collagen metabolism and contribute to POP. Studies indicate that cytokines such as IL-6, IL-10, and TGF, which are involved in inflammation, remodelling, and repair, have dual effects on POP and UI. They can promote tissue healing and regeneration but also exacerbate inflammation and fibrosis, contributing to the progression of these conditions. Understanding the dual roles of these cytokines could help us improve the vaginal microenvironment of women and treat POP and UI. Given the considerable changes in these cytokines, this review addresses studies published between 2000 and 2024 on the molecular mechanisms by which pro- and anti-inflammatory cytokines affect women with POP and UI. Furthermore, we explain novel therapeutic strategies for cytokine regulation, emphasizing the possibility of personalized treatments that address the underlying inflammatory milieu of the vagina in POP and UI patients. This thorough analysis aims to establish a foundation for future research and clinical applications, ultimately improving patient outcomes via designed cytokine-based therapies.